Exploring the crisis counseling process: a phenomenological study of guidance and school counselors’ experiences - Ismail, Yusnizal; Zakaria, Noor Syamilah; Puad Mohd Kari, Dharatun Nissa (Malque Publishing, 2025)
School counselors play a crucial role in addressing critical situations involving school children, such as mental health challenges, aggressive behaviors, and suicidal tendencies. The present research explores the lived experiences of school counselors in handling crisis counseling cases, focusing on their processes and strategies. However, managing crisis counseling in a school setting presents unique challenges due to time constraints, limited resources, and the complexity of student issues.The research was qualitative in nature, and the phenomenological approach involved semistructured interviews with 11 school counselors from secondary school in Malaysia. The data analysis was thematic using Atlas.ti 24 in order to identify emerging themes among their crisis counseling processes. As a result, there are five major themes which are school counselors’ self-preparation, information gathering, needs assessment, rapport building and crisis resolution and planning. This study underscores the need for crisis counseling models that are specifically designed for educational settings, considering the unique challenges school counselors face. The findings suggest that while existing intervention frameworks provide guidance, they may not fully address the distinct demands of school-based crisis counseling. Therefore, tailored models that integrate both psychological theories and practical school-based applications are essential to enhance crisis intervention effectiveness. Future research should prioritize developing and validating school-specific crisis counseling models. This includes assessing existing frameworks and designing context-specific approaches that align with real-life school counseling experiences. By advancing structured and effective intervention strategies, this research aims to better support students in crisis while equipping school counselors with essential tools for crisis management.